Flow affects the structural and mechanical properties of the fibrin network in plasma clots - Hande Eyisoylu; Emma D. Hazekamp; Janneke Cruts; Gijsje H. Koenderink; Moniek P. M. de Maat (Journal of Materials Science: Materials in Medicine)
Abstract The fibrin network is one of the main components of thrombi. Altered fibrin network properties are known to influence the development and progression of thrombotic disorders, at least partly through effects on the mechanical stability of fibrin. Most studies investigating the role of fibrin in thrombus properties prepare clots under static conditions, missing the influence of blood flow which is present in vivo. In this study, plasma clots in the presence and absence of flow were prepared inside a Chandler loop. Recitrated plasma from healthy donors were spun at 0 and 30 RPM. The clot structure was characterized using scanning electron microscopy and confocal microscopy and correlated with the stiffness measured by unconfined compression testing. We quantified fibrin fiber density, pore size, and fiber thickness and bulk stiffness at low and high strain values. Clots formed under flow had thinner fibrin fibers, smaller pores, and a denser fibrin network with higher stiffness values compared to clots formed in absence of flow. Our findings indicate that fluid flow is an essential factor to consider when developing physiologically relevant in vitro thrombus models used in researching thrombectomy outcomes or risk of embolization. Graphical Abstract